2021
DOI: 10.1111/icad.12528
|View full text |Cite
|
Sign up to set email alerts
|

‘Citizen identification’: online learning supports highly accurate species identification for insect‐focussed citizen science

Abstract: 1. Citizen science is widely used in ecological research. Data verification of citizen collected data continues to be an issue, and confirming accurate species identification reported by citizens can be especially difficult.2. Here, we determine the efficacy of using remote learning to identify UK social wasp (Vespinae) species. Citizen scientists (N = 559) collected wasps and identified specimens to species level using a series of online videos and support material.3. A pre-and post-identification questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…Of all investigated factors related to the individual respondent, training material resulted in the greatest decrease in misclassification rates. These results are similar to previous studies, which demonstrate that training material can improve quality of wildlife survey data (Ratnieks et al 2016;Katrak-Adefowora et al 2020;Perry et al 2021). Specifically, we saw the greatest reductions in error among adult males and fawns.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Of all investigated factors related to the individual respondent, training material resulted in the greatest decrease in misclassification rates. These results are similar to previous studies, which demonstrate that training material can improve quality of wildlife survey data (Ratnieks et al 2016;Katrak-Adefowora et al 2020;Perry et al 2021). Specifically, we saw the greatest reductions in error among adult males and fawns.…”
Section: Discussionsupporting
confidence: 90%
“…For example, practical training and educational materials are frequently provided to respondents of citizen science or volunteer-based projects with the intent of improving data reliability (Newman et al 2003;Cohn 2008;Steger et al 2017;Parsons et al 2018). Recent studies exploring the influence of longer-term (Danielsen et al 2014;van der Wal et al 2016) and single-session (Katrak-Adefowora et al 2020;Perry et al 2021) training programs on identifying wildlife images have generally found training to improve data reliability. However, the majority of previous research in this area has simply required respondents to classify wildlife images to the species level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of community science observation datasets has exponentially increased the availability of species occurrences for habitat suitability modelling (Bradter et al, 2018;Coxen et al, 2017;Jessica et al, 2014). Although the majority of such studies focus on vertebrate taxa, utilising community science data for insect SDMs is slowly gaining momentum (Perry et al, 2021). One of the more urgent endeavours of SDMs using community-science data is biodiversity conservation (Silva et al, 2013;Silva et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the UK's public were invited to hang a simple homemade bottle trap in their gardens for a week in late August and then post the samples to identification hubs where experts could verify species identity. Since 2020, participants have identified their own samples using online identification tools developed for the project (Perry et al, 2021). The project has proved highly successful in engaging with the public: between 2017 and 2021, 3389 unique participants/participant groups set out 7916 traps across the UK, catching over 62,000 wasps.…”
Section: Introductionmentioning
confidence: 99%